America's cold warrior Paul Nitze and national security from Roosevelt to Reagan - Wilson, James Graham 1980- (Cornell University Press, 2024)
"In America's Cold Warrior, James Graham Wilson traces Paul Nitze's career path in national security after World War II, a time when many of his mentors and peers returned to civilian life. Serving in eight presidential administrations, Nitze commanded White House attention even when he was out of government, especially with his withering criticism of Jimmy Carter during Carter's presidency. While Nitze is perhaps best known for leading the formulation of NSC-68, which Harry Truman signed in 1950, Wilson contends that Nitze's most significant contribution to American peace and security came in the painstaking work done in the 1980s to negotiate successful treaties with the Soviets to reduce nuclear weapons while simultaneously deflecting skeptics surrounding Ronald Reagan. America's Cold Warrior connects Nitze's career and concerns about strategic vulnerability to the post-9/11 era and the challenges of the 2020s, where the United States finds itself locked in geopolitical competition with the People's Republic of China and Russia."
Quellen- und Literaturverzeichnis: Seite 299-306, Register
Keywords: Nitze, Paul H. -- 1907-2004; Geschichte; Ost-West-Konflikt; Abschreckung; Sicherheitspolitik; USA; Nitze, Paul H / 1907-2004; National security / United States / History / 20th century; Cold War; Nuclear weapons / Government policy / United States; 20th century history: c 1900 to c 2000; United States / Officials and employees; United States / Military relations / Soviet Union; Soviet Union / Military relations / United States; United States / Foreign relations / 1945-1989